Journey to Diverse Microbial Worlds Adaptation to Exotic Environments - Seckbach, Joseph (Cellular Origin, Life in Extreme Habitats and Astrobiology, 2000)
In this Journey to Microbial Worlds we present the diversity of microorganisms, from the state of fossil microbes in Archaean age rocks to the possibilities of extraterrestrial life. This volume discusses the extremophiles living in harsh environments (from our anthropocentric point) and describes them in considerable detail. Some chapters also review topics such as symbiosis, bacterial luminescence, methanogens, and petroleum-grown cells. The final chapters of this book shed new light on astrobiology and speculate on extremophiles as candidates for extraterrestrial life. All chapters are updated to the latest research level